MRI and CT Assessment of Abdominal Tissue Composition in Patients After High-Intensity Focused Electromagnetic Therapy Treatments: One-Year Follow-Up. (27th February 2020) - Kinney, Brian M; Kent, David E
Abstract: Background: Several studies investigating high-intensity focused electromagnetic (HIFEM) treatments have recently been published. However, due to the novelty of the procedure, long-term data are still missing. Objectives: The aim of this study was to evaluate changes in abdominal tissues on average 1 year after a series of HIFEM treatments, to determine the long-term durability of patients' original body responses. Methods: Magnetic resonance imaging (MRI) or computed tomography (CT) scanning were performed on 21 patients a mean of 332.6 [88.5] days after their original HIFEM treatment series. The scans were evaluated by a blinded radiologist for abdominal muscle thickness, subcutaneous fat changes, and abdominal separation. The results were compared with the MRI/CT-assisted measurements taken at baseline and 6-week follow-up. Correlations between collected data sets were calculated and tested. The incidence of any adverse events related to earlier treatments was monitored. Results: When comparing the 1-year follow-up measurements with the baseline, the MRI/CT-assisted calculations revealed mean reductions of 14.63% (2.97 [2.11] mm) in fat, 19.05% (1.89 [0.88] mm) in muscle thickening, and 10.46% (1.96 [1.71] mm) in diastasis recti. All changes were significant ( P  < 0.05) and not related to weight fluctuations ( P  > 0.05). The baseline width of diastasis positively correlated with the degree of improvement at follow-up. No adverse events were reported. Conclusion: The HIFEM-induced muscle hypertrophy, fat reduction, and reduction in abdominal separation were maintained 1-year posttreatment. This suggests long-term durability of the original bodily response, which needs to be verified by continuing follow-up of this group and by further studies. Level of Evidence: 4: